Altmeric is Tool to Measure the Impact of Scholarly article: A Review. - Janen, T. (Bharathidasan University, 2017)
As scholarly communication and publishing models continue to increase, it is critical that those involved in the publication and dissemination of research, develop a good understanding of the changing environment in order to identify opportunities to improve how we understand the reach and influence of research. Different tools and metrics are used to measure the quality of scholarly work. Altmetric is a article level metric used to analysis how scholarship is being found, shared, cited, and discussed. This score reflects the overall attention that an article gets. This paper revealed that how the altmetric score can become as part of scholarly publishing. Key Words: Impact factor, Altmetric, and Article citation
Keywords: Impact Factor; Altmetric; Article citation